Completing Capital Mobilization Plan To Increase Revenue For Road Maintenance In Viet Nam - Dung, Nguyen Thi Tuyet; Hung, Bui Manh (International Journal of Psychosocial Rehabilitation, 2020)
Planning of road transport development in Vietnam to 2020 and vision to 2030 has emphasized the role of maintenance work in order to make the most of existing transport infrastructure capacity to ensure efficiency and sustainability in exploitation. The Government has also implemented numerous policies to mobilize investment capital for road maintenance and recorded some achievements (in the 2013-2017 period, the average capital allocated for national highway maintenance was VND 6,778.644 billion/year, many times higher than the period from 2009-2012 which was VND 2,615.13 billion/year). However, the limitations in planning to mobilize medium- and long-term capital make it difficult; granted capital for annual maintenance has not met the demand. Based on the analysis of existing capital and capital needs as well as the survey results, with the aid of SPSS software, the author has proposed solutions to complete capital mobilization planning through improving capacity for medium and long-term maintenance planning, which aims at increasing revenue for road maintenance.